Aminal‐Linked Porphyrinic Covalent Organic Framework for Rapid Photocatalytic Decontamination of Mustard‐Gas Simulant. Issue 32 (28th June 2022) - Wang, Qian‐You; Liu, Jing; Cao, Man; Hu, Jia‐Hua; Pang, Rui; Wang, Shan; Asad, Muhammad; Wei, Yong‐Li; Zang, Shuang‐Quan
Abstract: Covalent organic frameworks (COFs) are appealing photocatalysts for toxic chemical degradation. Great efforts have been devoted to regulate the photocatalytic performance of COFs by tuning their organic building blocks, but the relationship between COF linkage and photochemical properties has rarely been explored. Herein, we report the synthesis and characterisation of a novel aminal‐linked porphyrinic COF, namely Por‐Aminal‐COF. Por‐Aminal‐COF (0.25 mol %) showed excellent photocatalytic activity toward the detoxification of the sulfur mustard simulant with a half‐life ( t 1/2 ) of 5 min, which is far lower than that of traditional imine‐linked Por‐COF ( t 1/2 =16 min). Transient absorption spectroscopy indicated that the aminal linkages of Por‐Aminal‐COF facilitated the intersystem crossing process. Thus, Por‐Aminal‐COF showed higher triplet‐state generation efficiency compared with Por‐COF, consequently promoting the activation of oxygen molecular to singlet oxygen. Abstract : A novel aminal‐linked porphyrin‐based covalent organic framework (Por‐Aminal‐COF) was synthesized to detoxify the mustard‐gas simulant 2‐chloroethyl ethyl sulfide (CEES). Compared with imine‐linked Por‐COF, Por‐Aminal‐COF demonstrates higher photooxidation of CEES into 2‐chloroethyl ethyl sulfoxide (CEESO). The COF linkages contribute to an intersystem crossing process and enhance the photochemical properties of the catalyst.